Sulfatides regulate specific uptake of liposomes by an astrocytoma cell line (2017)
Glioblastoma multiforme (GBM) is one of the most aggressive forms of central nervous System (CNS) neoplasm, and corresponds to 77% of brain tumors. Despite substantial advances in the development of new cancer treatments, GBM remains a tumor of dificult treatment and poor prognosis. Among the current therapeutic strategies, chemotherapy is the most frequently used alone or in combination with other therapies. However drawbacks related with an eficient delivery of the therapeutic agent to the tumor cells limit their success. A promising approach is to implement novel delivery systems using carriers which transport molecules in the body and across barriers such as the blood brain barrier, ensuring drug accumulation in tumor tissue. Among these carners, liposomes have received special attention since their physicochemical properties may be modifiable for specific targets while minimizing side effects. GBM tumors over-express Iow-density lipoprotein receptor (LDLR), so targeting this receptor is a rational avenue for potential therapies